Obesity and Breast Cancer Risk in Men: A National Case-Control Study in England and Wales. Issue 5 (28th August 2021) - Swerdlow, Anthony J; Bruce, Cydney; Cooke, Rosie; Coulson, Penny; Griffin, James; Butlin, Alison; Smith, Beverley; Swerdlow, M Jill; Jones, Michael E
Abstract: Background: Breast cancer is rare in men, and information on its causes is very limited from studies that have generally been small. Adult obesity has been shown as a risk factor, but more detailed anthropometric relations have not been investigated. Methods: We conducted an interview population-based case-control study of breast cancer in men in England and Wales including 1998 cases incident during 2005-2017 at ages younger than 80 years and 1597 male controls, with questions asked about a range of anthropometric variables at several ages. All tests of statistical significance were 2-sided. Results: Risk of breast cancer statistically significantly increased with increasing body mass index (BMI) at ages 20 (odds ratio [OR] = 1.07, 95% confidence interval [CI] = 1.02 to 1.12 per 2-unit change in BMI), 40 (OR = 1.11, 95% CI = 1.07 to 1.16), and 60 (OR = 1.14, 95% CI = 1.09 to 1.19) years, but there was also an indication of raised risk for the lowest BMIs. Large waist circumference 5 years before interview was more strongly associated than was BMI with risk, and each showed independent associations. Associations were similar for invasive and in situ tumors separately and stronger for HER2-positive than HER2-negative tumors. Of the tumors, 99% were estrogen receptor positive. Conclusions: Obesity at all adult ages, particularly recent abdominal obesity, is associated with raised risk of breast cancer in men, probably because of the conversion of testosterone to estrogen by aromatase in adipose tissue. The association is particularly strong for HER2-expressing tumors.